The Role of Transport and Logistics Components of Mongolia in the Development of Euro-Asian Economic Cooperation - Avirmed, Davaasuren; Huang, Tonglaga (Mongolian Journal of International Affairs, 2023)
This article assesses the implementation of Mongolia's “New Recovery Policy”, evaluates the current status of cargo and passenger transport, analyzes the impact of the Covid-19 pandemic on these sectors, and identifies issues within the transport and logistics industry. Following the research, three primary conclusions were drawn: firstly, proposing actual solutions to the problems mentioned in this study; secondly, to augment transit traffic passing through Mongolia; and thirdly, the establishment of an autonomous government body, crucial for creating the central economic corridor connecting China, Mongolia, and Russia. The proposal suggests establishing an analysis institute to coordinate medium and long-term development policies of Russia and China, manage projects in the transport infrastructure domain, align legal frameworks among the three nations, and oversee the construction of the corridor.